Commodity risk assessment of Petunia spp. and Calibrachoa spp. unrooted cuttings from Kenya - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; et al. (EFSA Journal, 2024)
Abstract The European Commission requested the EFSA Panel on Plant Health to evaluate the probability of entry of pests (likelihood of pest freedom at entry), including both regulated and non‐regulated pests, associated with unrooted cuttings of the genera Petunia and Calibrachoa produced under physical isolation in Kenya. The relevance of any pest for this opinion was based on evidence following defined criteria, based on the methodology used for High‐Risk Plants adapted for the specificity of this assessment. Sixteen EU‐regulated pests (Bemisia tabaci, cowpea mild mottle virus, Liriomyza huidobrensis, Liriomyza sativae, Liriomyza trifolii, potato leafroll virus, potato virus S, potato virus X, potato spindle tuber viroid, Ralstonia pseudosolanacearum, R. solanacearum, Scirtothrips dorsalis, tomato mild mottle virus, tomato spotted wilt virus, tomato yellow leaf curl virus and Xanthomonas vesicatoria) and six EU non‐regulated pests (Aleurodicus dispersus, pepper veinal mottle virus, Nipaecoccus viridis, Phenacoccus solenopsis, Tetranychus neocaledonicus and tomato yellow ring virus) fulfilled all relevant criteria and were selected for further evaluation. For these pests, the risk mitigation measures proposed in the technical dossier from Kenya were evaluated, taking into account the possible limiting factors. Additionally, an expert judgement is given on the likelihood of pest freedom, taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The estimated degree of pest freedom varies among the pests evaluated, with T. neocaledonicus being the pest most frequently expected on the imported cuttings. The Expert Knowledge Elicitation indicated, with 95% certainty, that between 9942 and 10,000 bags containing unrooted cuttings of Petunia spp. and Calibrachoa spp. per 10,000 would be free of T. neocaledonicus.